Development of a new code family based on SAC-OCDMA system with large cardinality for OCDMA network - Thanaa Hussein, Abd; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Hilal Adnan, Fadhil; R. A., Ahmad; Mohamad Naufal, Mohamad Saad, Dr. (Elsevier Inc., 2011)
Link to publisher's homepage at http://www.elsevier.com/